PENGARUH PERBANDINGAN TEPUNG BERAS (Oryza sativa) DAN LABU KUNING (Cucurbita moschata Durch) TERHADAP KARAKTERISTIK SUMPING LABU - Amalia, Aini; Jambe, Anak Agung Gede Ngurah Anom; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
The purposes of this research were to know the effect of rice flour and pumpkin ratio on the characteristics of sumping and to find the right ratio from rice flour  and pumpkin to produce sumping with the best characteristics. The completely randomized design was used in the research with treatment that is the ratio rice flour with pumpkin which consist of 25% : 75%; 30% : 70%; 35% : 65%; 40% : 60%; 45% : 55%; 50% : 50%. The treatment was repeated 3 times to obtained 18 units. The data obtained were analyzed of variance and if the treatment had an effect on the variable then continued with Duncan test. The results showed that rice flour and pumpkin ratio had significant effect to water content, ash content, total caroten, skoring test (colour, aroma, texture, taste) and hedonic test (colour, aroma, texture, taste, and overall acceptance). The ratio of rice flour 25 % and pumpkin 75%  produces with the best characteristic namely water content 57,55%, ash content 1,74%, total caroten content 10868,52 ?g/g, color yellow and like, flavor pumkin typical and rather like, texture chewy and like, taste typical pumkin and like and overall acceptance like. Keywords : Rice flour, p umpkin , p umpkin sumping